One size does not fit all: the need for individualized treatment based on factors that may affect the therapeutic outcome of efinaconazole 10% solution for the treatment of toenail onychomycosis. (3rd July 2021) - Gupta, Aditya K.; Venkataraman, Maanasa; Anbalagan, Naveen; Guenin, Eric P.
Abstract: Successful management of onychomycosis is a challenge because cure rates with most antifungals are relatively low and recurrence rates are high. A drug‐based approach by treating the nail alone may not suffice. There are several host‐related factors (age, sex, body mass index [BMI], and patient's quality of life), disease‐related factors (disease severity, duration, and the number of toenails affected), and comorbidities (tinea pedis and diabetes) that may affect treatment efficacy. Here, we review the post hoc analyses of the phase III trials of efinaconazole 10% solution that have investigated the impact of these factors on topical therapy for toenail onychomycosis. The significant clinical variables that may affect the efficacy of efinaconazole include sex, BMI, disease severity, disease duration, and tinea pedis. As older patients may have slower toenail growth and more severe, longstanding disease compared with younger patients, they may require longer treatment duration, beyond the 48‐week standard regimen. Treatment compliance may need to be discussed for an improved health outcome. Therefore, these prognostic factors need to be carefully evaluated, which may aid in formulating individualized therapy to maximize treatment success.